Coexistence of detonation with deflagration in rotating detonation engines. (24th August 2016) - Wang, Yuhui; Wang, Jianping
Abstract: Rotating detonation engines of high thermal efficiency and specific impulse have been studied a lot. However, rotating detonation waves lead to uneven flow field, local high temperature and high pressure, tending to damage the combustor. An experimental way to keep both rotating detonation waves and deflagration in the combustor and to combine the advantages of rotating detonation engines and deflagration engines, is introduced here. Pressure sensors measure the pressure of rotating detonation waves and gas mass flow controllers control the mass flow rates of reactants. A standard speed camera captures the events of rotating detonation and deflagration. It is discovered that the rotating detonation is much more intense than deflagration. Both upstream rotating detonation waves and downstream deflagration respectively dependent on the trunk stream and the tributary can coexist in the combustor. The predetonator is the boundary between the detonation region and deflagration region in the combustor. The coexistence of detonation and deflagration weakens the combustion instability caused by rotating detonation, which may be helpful for rotating detonation to be applied. Highlights: Rotating detonation and deflagration can coexist in detonation engines. Rotating detonation is more intense than deflagration. Rotating detonation or deflagration in an engine is steerable.